Metodologia ETECS: desenvolvendo soluções inovadoras nas compras públicas - Silva, Ívina Mariana Duarte Marinho e (2024)
Innovative public contracts are fundamental tools in demand- and mission-oriented innovation policy. Instruments of significant public expenditure globally amount to over 15% of the world GDP, 19.5% in Europe, and approximately 12% of the Brazilian GDP. This dissertation aims to develop and propose an innovative methodology to guide innovation projects directed at public procurement. This research is applied, and as a methodological approach, it combined research and development techniques with policy research techniques. It utilized benchmarking methods of global practices, technological foresight, and trend mapping. As a result, a new accessible and replicable methodological solution is presented to enhance innovation management in solutions addressed to innovative public procurement. The proposed methodological solution was evaluated in a specific application, and its potential benefits for future applications were discussed. The final report emphasizes the need for policy implications and development models for the effective implementation of innovative public contracts as a national strategy, highlighting their importance as essential instruments of economic and innovation policy.